2014
DOI: 10.1080/02699931.2014.917071
|View full text |Cite
|
Sign up to set email alerts
|

The language of worry: Examining linguistic elements of worry models

Abstract: Despite strong evidence that worry is a verbal process, studies examining linguistic features in individuals with generalised anxiety disorder (GAD) are lacking. The aim of the present study is to investigate language use in individuals with GAD and controls based on GAD and worry theoretical models. More specifically, the degree to which linguistic elements of the avoidance and intolerance of uncertainty worry models can predict diagnostic status was analysed. Participants were 19 women diagnosed with GAD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Instead, a focus on the present emerged as the linguistic feature that most prominently and positively correlates with GAD (33). This finding, however, is at odds with an earlier study in clinical setting, in which the spoken language of women diagnosed with GAD was linked to lower use of present, and higher use of future, verb tense (34). These findings may be attributed to platform-specific characteristics and inherent differences between written and spoken language, but they also illustrate how little consensus exists regarding the verbal linguistic markers of GAD.…”
Section: The Verbal-linguistic Nature Of Worry and Gadcontrasting
confidence: 65%
“…Instead, a focus on the present emerged as the linguistic feature that most prominently and positively correlates with GAD (33). This finding, however, is at odds with an earlier study in clinical setting, in which the spoken language of women diagnosed with GAD was linked to lower use of present, and higher use of future, verb tense (34). These findings may be attributed to platform-specific characteristics and inherent differences between written and spoken language, but they also illustrate how little consensus exists regarding the verbal linguistic markers of GAD.…”
Section: The Verbal-linguistic Nature Of Worry and Gadcontrasting
confidence: 65%
“…Recent developments in computerized text analysis have shown that counting the specific types of words that people naturally use, also called quantitative word count analysis, provides important information about their psychological health and adjustment (23,24,40). Word use has been found to differentiate between formerly, never, and currently depressed students (43) and to discriminate women with and without generalized anxiety disorder (13); it has also been found to be a marker of suicidal ideation (46), adjustment to breast cancer (40), and psychological change surrounding traumatic events (5,28,35). …”
Section: Introductionmentioning
confidence: 99%
“…Findings from regression analyses indicate that those with higher activity engagement express fewer first-person plural pronouns but more other-person referring pronouns. Previous literature showing that individuals with depressed and anxious symptoms, higher suicidal ideation, and greater pain catastrophizing tend to speak with the greater use of first person singular pronouns (Geronimi & Woodruff-Borden, 2015;Handelman & Lester, 2007;Junghaenel et al, 2017) raises the possibility that this pattern may reflect lower levels of self-expression of distress and pain among those with higher pain acceptance. The findings of a higher use of first-person and other-focused pronouns among those with higher pain catastrophizing were interpreted in the context of the communal coping model, which posits that individuals with high pain catastrophizing likely engage in exaggerated pain expression to solicit social support (Sullivan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Computerized text analysis (e.g., Linguistic Inquiry and Word Count [LIWC]; Pennebaker, Booth, et al, 2015) provides quantitative word counts and linguistic categories, which help us better understand one’s cognitive-emotional processes. LIWC has been used to differentiate people with symptoms of depression or anxiety from those without them (Geronimi & Woodruff-Borden, 2015), identify people at high risk for suicide (Handelman & Lester, 2007), measure verbal expressions of emotion (Jasinski et al, 2016; Kahn et al, 2007), and understand psychological and social changes to interactive behavior involved in traumatic experiences (Cohn et al, 2004; Mehl & Pennebaker, 2003; Pennebaker et al, 1997). LIWC has also been used to identify linguistic indicators to predict healthy family adjustment following breast cancer (Robbins et al, 2013) and an effective communication style of physicians who work with patients with chronic pain (Shields et al, 2013).…”
Section: Introductionmentioning
confidence: 99%